2021
DOI: 10.1093/cdj/bsab028
|View full text |Cite
|
Sign up to set email alerts
|

Community development and social work teaching and learning in a time of global interruption

Abstract: In a rapidly changing and unpredictable global environment, there is new impetus to draw on community development approaches in the face of complex practice challenges that include the long-term impacts of the COVID-19 pandemic. As social work and community development educators in Ireland and Australia, the question becomes how can we respond in a time of major ‘disruption’ where there are both opportunities and constraints? This paper settles on this pause and uncertainty to seek new approaches to prepare so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Operations in social field practices include, among others, empowering people, helping, communicating, assessing, providing social service, collaborating, and leading change process-but also making use of a large measure of creativity [2,6,22,27]. These types of professional positions, actions, and roles have been described in Michael Lipsky's concept as front-line bureaucrats or street-level bureaucrats [28].…”
Section: Creativity In a Professional Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Operations in social field practices include, among others, empowering people, helping, communicating, assessing, providing social service, collaborating, and leading change process-but also making use of a large measure of creativity [2,6,22,27]. These types of professional positions, actions, and roles have been described in Michael Lipsky's concept as front-line bureaucrats or street-level bureaucrats [28].…”
Section: Creativity In a Professional Spacementioning
confidence: 99%
“…Studies of the role of intuition in educational creativity contexts found intuition understood as specific way of knowing, one that does not really articulate the origin of how a specific situation or subject is perceived [3,27,31]. The integrative phase in this project was, in the beginning, dealing with some of the occurring problems more intuitively than cognitively, for example, viewing problems solution as hypotheses.…”
Section: Integrative Creativitymentioning
confidence: 99%
“…Climate change and environmental sustainability are issues which have begun to capture the social work imagination across both scholarship and practice and an array of contributions made in recent years demonstrates this (Boetto et al, 2020;Harris & Boddy, 2017;Holbrook et al, 2019;Lucas-Darby, 2011;Lynch et al, 2021;Noble, 2016;Philip & Reisch, 2015;Ranta-Tyrkko & Narhi, 2021). (Whelan, 2022b).…”
Section: Sustainability and Social Workmentioning
confidence: 99%